Training and Assistance in Making Ginger Basic Ingredients-Healthy Candy in Increasing Family Income - Indrayani, Yuliati (Universitas Nurul Jadid, 2024)
The people of Peniti Besar Village, Segedong District, Mempawah Regency, are aware of planting various spice plants, including ginger. So far, ginger is used as a spice in dishes and drinks or sold as fresh ginger with low selling value. This service activity aims to improve community knowledge and skills in processing ginger as a health candy that can be used as a business opportunity to increase family income. The method used is training in material delivery, discussion, and practice of making ginger candy. Partners as training participants were P.K.K. members, totaling 25 people. The evaluation results showed that partners welcomed the training activities. The knowledge and skills of the community-made ginger candy increased by 86.64%, from 13.36% (before attending the training) to 100% (after attending the training). People want to make ginger candy (100%) and sell it (92%) so that it can increase family income.